Rethinking the law school education, research, outreach and governance - Stolker, C.J.J.M (Cambridge University Press, 2014)
Law, by its very nature, tends to think locally, not globally. This book has a broader scope in terms of the range of nations and offers a succinct journey through law schools on different continents and subject matters. It covers education, research, impact and societal outreach, and governance. It illustrates that law schools throughout the world have much in common in terms of values, duties, challenges, ambitions and hopes. It provides insights into these aspirations, whilst presenting a thought provoking discussion for a more global agenda on the future of law schools. Written from the perspective of a former dean, the book offers a unique understanding of the challenges facing legal education and research.